1996
DOI: 10.1016/1044-0305(95)00604-4
|View full text |Cite
|
Sign up to set email alerts
|

The importance of charge-separation reactions in tandem mass spectrometry of doubly protonated angiotensin II formed by electrospray ionization: Experimental considerations and structural implications

Abstract: The occurrence of charge-separation reactions in tandem mass spectrometry of doubly protonated angiotensin II is demonstrated by the use of mass-analyzed ion kinetic energy spectrometry (MIKES) and kinetic energy release distributions (KERDs). Linked scans at a constant B/E severely discriminate against product ions formed by charge-separation reactions. Although the products are significantly more abundant in MIKES experiments, instrumental discrimination still makes quantitation of relative product ion abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 83 publications
5
36
0
Order By: Relevance
“…The results showed little variation with collision energy at the lower collision energies which were used to derive the data of ties. In agreement with the analysis of Zubarev and coworkers [11] symmetric cleavage of the second amide bond dominates for smaller peptides but decreases substantially in importance as the peptide size increases and is not the dominant cleavage mode for doublyprotonated (Ala) 10 His. Paizs and coworkers [13] also observed that symmetric cleavage of the second amide bond was the dominant fragmentation mode for doublyprotonated (Gly) 5 Arg.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The results showed little variation with collision energy at the lower collision energies which were used to derive the data of ties. In agreement with the analysis of Zubarev and coworkers [11] symmetric cleavage of the second amide bond dominates for smaller peptides but decreases substantially in importance as the peptide size increases and is not the dominant cleavage mode for doublyprotonated (Ala) 10 His. Paizs and coworkers [13] also observed that symmetric cleavage of the second amide bond was the dominant fragmentation mode for doublyprotonated (Gly) 5 Arg.…”
Section: Resultssupporting
confidence: 88%
“…In all cases these asymmetric amide bond cleavages occur near the N-terminus of the peptide. Thus, (Ala) 5 His shows a weak signal for y 5 ϩ2 , (Ala) 6 His shows weak signals for y 5 ϩ2 and y 6 ϩ2 , (Ala) 7 His shows weak signals for y 6 ϩ2 and y 7 ϩ2 , (Ala) 8 His shows weak signals for y 7 ϩ2 and y 8 ϩ2 while (Ala) 10 His shows a signal for y 9 ϩ2 and a very weak signal at m/z 398 corresponding to y 10 ϩ2 . The primary b and y ions undergo further fragmentation, particularly at higher collision energies.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…10. This indicates that the y 2 /b 5 ion pair is complementary, consistent with conclusions for the y 2 /b 5 ions of doubly-protonated angiotensin II (DRVYIHPF) using kinetic energy release distributions (KERDs) [45]. While scrambling of the deuterium atoms before or during the fragmentation event cannot be ruled-out, the partitioning of the deuterium atoms demonstrates that both fragment ions are being formed by the same mechanism.…”
Section: Fragmentation Of [Rvyifpf + 2h] 2+ Ion Populations Labeled Bsupporting
confidence: 75%